An instrument for assessing the quality of informed consent documents for elective procedures: development and testing. Issue 5 (19th May 2020) - Spatz, Erica S; Suter, Lisa G; George, Elizabeth; Perez, Mallory; Curry, Leslie; Desai, Vrunda; Bao, Haikun; Geary, Lori L; Herrin, Jeph; Lin, Zhenqiu; Bernheim, Susannah M; Krumholz, Harlan M
Abstract : Objective: To develop a nationally applicable tool for assessing the quality of informed consent documents for elective procedures. Design: Mixed qualitative-quantitative approach. Setting: Convened seven meetings with stakeholders to obtain input and feedback on the tool. Participants: Team of physician investigators, measure development experts, and a working group of nine patients and patient advocates (caregivers, advocates for vulnerable populations and patient safety experts) from different regions of the country. Interventions: With stakeholder input, we identified elements of high-quality informed consent documents, aggregated into three domains: content, presentation and timing. Based on this comprehensive taxonomy of key elements, we convened the working group to offer input on the development of an abstraction tool to assess the quality of informed consent documents in three phases: (1) selecting the highest-priority elements to be operationalised as items in the tool; (2) iteratively refining and testing the tool using a sample of qualifying informed consent documents from eight hospitals; and (3) developing a scoring approach for the tool. Finally, we tested the reliability of the tool in a subsample of 250 informed consent documents from 25 additional hospitals. Outcomes: Abstraction tool to evaluate the quality of informed consent documents. Results: We identified 53 elements of informed consent quality; of these, 15 were selected as highest priority for inclusion in the abstraction tool and 8 were feasible to measure. After seven cycles of iterative development and testing of survey items, and development and refinement of a training manual, two trained raters achieved high item-level agreement, ranging from 92% to 100%. Conclusions: We identified key quality elements of an informed consent document and operationalised the highest-priority elements to define a minimum standard for informed consent documents. This tool is a starting point that can enable hospitals and other providers to evaluate and improve the quality of informed consent.